Impact of shift work and other work-related factors on anti-SARS-CoV-2 spike-protein serum concentrations in healthcare workers after primary mRNA vaccination – a retrospective cohort study (Swiss Medical Weekly, 2024)
BACKGROUND: Knowing whether shift work negatively affects the immune system’s response to COVID-19 vaccinations could be valuable for planning future vaccination campaigns for healthcare workers. We aimed to determine the impact of working late or night shifts on serum anti-SARS-CoV-2 spike protein immunoglobulin G (anti-S) antibody levels after primary SARS-CoV-2-mRNA vaccination.METHODS: To obtain detailed information on shift work, we sent a separate online questionnaire to 1475 eligible healthcare workers who participated in a prospective longitudinal study conducted in 15 healthcare institutions in Switzerland. We asked all vaccinated healthcare workers with available anti-S antibody levels after vaccination to complete a brief online survey on their working schedules within one week before and after primary mRNA vaccination. We used multivariate regression to evaluate the association between work shifts around primary vaccination and anti-S antibody levels. We adjusted for confounders already known to influence vaccine efficacy (e.g. age, sex, immunosuppression, and obesity) and for variables significant at the 0.05 alpha level in the univariate analyses.RESULTS: The survey response rate was 43% (n = 638). Ninety-eight responders were excluded due to unknown vaccination dates, different vaccines, or administration of the second dose shortly (within 14 days) after or before serologic follow-up. Of the 540 healthcare workers included in our analysis, 175 (32.4%) had worked at least one late or night shift within seven days before and/or after primary vaccination. In the univariate analyses, working late or night shifts was associated with a nonsignificant −15.1% decrease in serum anti-S antibody levels (p = 0.090). In the multivariate analysis, prior infection (197.2% increase; p